2019
DOI: 10.1007/s11666-019-00888-8
|View full text |Cite
|
Sign up to set email alerts
|

A Computational and Experimental Investigation into Radial Injection for Suspension High Velocity Oxy-Fuel (SHVOF) Thermal Spray

Abstract: Suspension high velocity oxy-fuel thermal spray typically utilizes axial injections of suspension into the combustion chamber. There are certain cases where the oxygen-sensitive nanoparticles benefit from a reduction in the time and temperature spent in the gas flow. Therefore, a radial injection outside of the nozzle can enable deposition of oxygen-sensitive nanomaterials. This study investigated the effect of the suspension flow rate, angle of injection and the injector diameter on the in-flight particle con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Therefore, it should be taken into account that even if higher values are reached at 75 kW, these could refer to a smaller fraction of particles compared to the 50 kW and 25 kW case. Additional considerations on these measured values can be made upon comparison with flame temperature and velocity values simulated using the eddy dissipation concept model from a recently published work on this same HVOF setup [20]. According to these simulations, the 75 kW flame at 100 mm stand-off distance is characterized by a gas temperature and velocity around 1800…”
Section: In-flight Temperature and Velocity Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it should be taken into account that even if higher values are reached at 75 kW, these could refer to a smaller fraction of particles compared to the 50 kW and 25 kW case. Additional considerations on these measured values can be made upon comparison with flame temperature and velocity values simulated using the eddy dissipation concept model from a recently published work on this same HVOF setup [20]. According to these simulations, the 75 kW flame at 100 mm stand-off distance is characterized by a gas temperature and velocity around 1800…”
Section: In-flight Temperature and Velocity Measurementsmentioning
confidence: 99%
“…The stand-off distances used in S-HVOF thermal spray are normally much shorter than those used in this work, at around 85 mm. Such a short stand-off distance proves unsuitable for GNP spray since the hot jet (1850 °C at 85 mm for a 75 kW flame [20]), as it sweeps the substrate surface, transfers an amount of heat that accumulates on the sample and which GNPs are not able to withstand and may degrade. Moreover, the combustion jet from the S-HVOF thermal spray gun is capable of mechanically removing the loosely bonded GNPs from the substrate surface, hence lowering the deposition efficiency.…”
Section: Gnp Thin Film Depositionmentioning
confidence: 99%
“…It was found that the suspension penetration becomes more efficient and higher particle velocity and temperature can be obtained if the injector is near the torch exit and its angle is toward the torch [12]. The stated suspension model has been used by several researchers so far to simulate different suspension thermal spray processes, and its accuracy and reliability have been verified under various operating conditions [12][13][14][15][16][17][18][19][20][21][22]. For instance, Pourang et al [13] used the mentioned approach and analyzed the temporal evolution of a 40 µm suspension droplet containing zirconia (10 wt.%) and After the suspension breakup, the liquid evaporation becomes dominant.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that suspension penetration depth, as well as droplet/particle trajectory, temperature, and velocity, are a strong function of plasma jet fluctuations and injection properties such as injection velocity. In addition to the SPS simulations, the stated model was successfully used by Jadidi et al [19,20] and Chadha et al [21,22] to model suspension high-velocity oxygen-fuel (HVOF) process as well. It should be pointed out that for simulating suspension HVOF, the Taylor Analogy Breakup (TAB) model was used to model the droplet breakup since the Weber number is relatively low in this process.…”
Section: Introductionmentioning
confidence: 99%
“…This is an open access article under the CC BY license ( http://creativecommons.org/licenses/by/4.0/ ) ( Esther Dongmo et al, 2009 ;Jadidi et al, 2016 ). Traditionally, the blob method is employed to model the injection of suspension into the combustion chamber ( Chadha et al, 2019b ;Chadha et al, 2019a ). For the blob method the jet is simplified to an injection of discrete droplets that can undergo secondary breakup.…”
Section: Introductionmentioning
confidence: 99%